ANALISA STRATEGI IT DENGAN PENDEKATAN SWOT PADA UKM - Laela Kurniawati (LPPM STMIK Antar Bangsa, 2015)
Abstract—Application of information technology systems in an SME engaged in the sale of children's clothes would be beneficial if the application in accordance with the purpose, vision andthe organization's mission to establish a business strategy and information technology systems strategy. And so we need an analysis of various factors that influence the formation of a strategic planning system or information technology adaptabledan aligned with business strategy. Issues to be addressed in this study is whether the strategy of information technology systems for SMEs engaged in the sale of clothing online shop based child so that the SMEs can become one of competitive SMEs, while the purpose of this study was to determine the strategy of the current system. Then dala this occasion, will be analyzed informsi technology system based on SWOT analysis systems.The result of research are the first, SWOT Matrix can be used to develop a variety of strategies to strengthen conditions of SMEs, second, Based on the results of SWOT analysis is a small gallery on growth strategy, and third, results of internal matrix processing strategy used is the strategy of growth. Intisari— Penerapan sistem teknologi informasi pada sebuah UKM yang bergerak di bidang penjualan baju anak akan bermanfaat jika penerapannya sesuai dengan tujuan, visi dan misi organisasi dengan menetapkan strategi bisnis dan strategi sistem teknologi informasi. Sehingga dibutuhkan suatu analisa berbagai faktor yang mempengaruhi terbentuknya suatu perencanaan strategi sistem atau teknologi informasi yang adaptable dan selaras dengan strategi bisnis. Permasalahan yang akan dibahas dalam penelitian ini yaitu apakah strategi sistem teknologi informasi bagi UKM yang bergerak di bidang penjualan baju anak berbasis online shop agar UKM tersebut bisa menjadi salah satu UKM yang kompetitif, sedangkan tujuan dari penelitian ini adalah untuk mengetahui strategi sistem saat ini. Maka dalam kesempatan ini, akan dilakukan analisa sistem teknologi informasi berdasarkan analisa sistem SWOT. Hasil penelitian yang didapat yaitu: pertama, matrik SWOT dapat digunakan untuk menyusun berbagai strategi untuk memperkuat kondisi UKM. Kedua, berdasarkan hasil dari analisa SWOT galeri kecil berada pada strategi pertumbuhan, dan ketiga, hasil pengolahan matrik internal strategi yang dipakai adalah strategi growth.